ANALISA PENGARUH PENAMBAHAN SERAT BAJA TERHADAP SIFAT MEKANIK BETON NORMAL - Yuniarsa Amelia (PT LIB Research Cendekia, 2026)
Concrete is the most widely used construction material due to its high compressive strength, but its weaknesses lie in its low tensile strength and brittle nature. One effort that can be done to improve the mechanical properties of concrete, especially tensile strength, is by adding steel fiber to the concrete mixture. This study aims to analyze the effect of variations in steel fiber addition on the mechanical properties of normal concrete, so that it is expected to produce concrete with better structural performance and resistance to cracking. This study aims to analyze the effect of varying steel fiber addition on the mechanical properties of normal concrete, specifically on the compressive and splitting tensile strength of concrete. The variations in steel fiber content used in this study were 0%, 0.7%, and 1% of the concrete volume. Testing was conducted on cylindrical specimens with a diameter of 15 cm and a height of 30 cm after curing for 14 days. The results of the study indicate that the addition of steel fibers has an effect on improving the mechanical properties of normal concrete. The slump value decreases with increasing steel fiber content, which indicates a decrease in the workability of the concrete mixture. Optimum compressive strength is obtained at the addition of 0.7% steel fiber, while optimum splitting tensile strength is achieved at the addition of 1% steel fiber. Overall, the use of steel fibers in concrete mixtures can increase crack resistance and improve the mechanical behavior of concrete, so it can be used as an alternative additive to improve the structural performance of normal concrete.